Do fertility treatments affect labor induction success rate? A retrospective cohort study. (3rd June 2022) - Gat, Itai; Barzilay, Eran; Zemet, Roni; Mohr-Sasson, Aya; Kedem, Alon; Orvieto, Raoul; Hass, Jigal
Abstract: Purpose: To evaluate labor induction success rate by Foley catheter (FC) on patients who conceived spontaneously, as compared to those who underwent fertility treatments. Materials and methods: This retrospective cohort study included all pregnant women hospitalized at a single tertiary care center between January 2011 and May 2018 for induction of labor with FC. The study groups included patients with a singleton pregnancy who conceived after fertility treatments: controlled ovarian hyperstimulation (COH) or in vitro fertilization (IVF), while control group included patients who conceived spontaneously. Our primary outcome was the rate of cesarean deliveries. Regression analysis was conducted on the following parameters: age, gravidity, parity, the gestational week, and IVF. Results: The study groups included 59, 321, and 3159 patients who conceived following COH, IVF, or spontaneously, respectively. While 72.1% of patients who conceived spontaneously had a vaginal delivery, only 62.7% and 58% of patients who conceived by COH and IVF had successful labor induction (respectively, p  < .01). Similarly, significantly higher cesarean section (CS) rates were demonstrated by patients who conceived by COH and IVF (28.8% and 30%, respectively), compared to the control group (18.7%, p  < .01). Regression analysis demonstrated that although age, parity, and the gestational week were significantly related to cesarean sections, no statistically significant association was found regarding fertility treatments ( p  = .050). Conclusions: The possible association between fertility treatments and cesarean delivery remains an important dilemma for obstetricians and fertility experts. While unadjusted analysis demonstrated such association among patients who undergo labor induction by FC, adjusted analysis has not supported that finding. Further studies focusing on the causes of failed vaginal delivery are needed to further expand our knowledge and to improve patient consultation.